Thermo-energetic design of machine tools : a systemic approach to solve the conflict between power efficiency, accuracy and productivity demonstrated at the example of machining production /: a systemic approach to solve the conflict between power efficiency, accuracy and productivity demonstrated at the example of machining production. ([2014]) - Unknown
No abstract available